PENERAPAN GRAF PADA PERSIMPANGAN MENGGUNAKAN ALGORITMA WELSH-POWEL UNTUK OPTIMALISASI PENGATURAN TRAFFIC LIGHT - Setiawan, Danang Aji; Suyitno, Amin; Arifudin, Riza (Universitas Negeri Semarang, 2016)
The purpose of this study are to determine (1) the application of the intersection graph using Welsh-Powell algorithm for optimizing traffic light setting and (2) simulating traffic light settings using Microsoft Visual Basic 6.0. The method used includes several stages, namely data collection, processing and analysis of data, the manufacturing simulation, and conclusion. From the results of the analysis showed that the results of the calculation for the Jerakah intersection no more effective than primary data due at the intersection of the most effective own calculations have been made by DISHUBKOMINFO of Semarang and intersection calculations for STIKES Tlogorejo produce better effectiveness of primary data so that the calculations have been made suitable to be applied to the intersection. Making the simulation to present the case of setting the traffic light at the Jerakah intersection and at the STIKES Tlogorejo intersection in visual form so that the resolution of the easier and shorter, because the duration of the simulation can include a red light, yellow light, and green light by random